Achievement of Paris climate goals unlikely due to time lags in the land system - Brown, Calum; Alexander, Peter; Arneth, Almut; Holman, Ian P.; Rounsevell, Mark (Nature Publishing Group, 2019)
Achieving the Paris Agreement’s aim of limiting average global temperature increases to 1.5 °C requires substantial changes in the land system. However, individual countries’ plans to accomplish these changes remain vague, almost certainly insufficient and unlikely to be implemented in full. These shortcomings are partially the result of avoidable ‘blind spots’ relating to time lags inherent in the implementation of land-based mitigation strategies. Key blind spots include inconsistencies between different land-system policies, spatial and temporal lags in land-system change, and detrimental consequences of some mitigation options. We suggest that improved recognition of these processes is necessary to identify achievable mitigation actions, avoiding excessively optimistic assumptions and consequent policy failures.